Host Immune Responses and Immune Evasion Strategies in African Trypanosomiasis - Onyilagha, Chukwunonso; Uzonna, Jude Ezeh (Frontiers in Immunology, 2019)
Parasites, including African trypanosomes, utilize several immune evasion strategies to ensure their survival and completion of their life cycles within their hosts. The defense factors activated by the host to resolve inflammation and restore homeostasis during active infection could be exploited and/or manipulated by the parasites in an attempt to ensure their survival and propagation. This often results in the parasites evading the host immune responses as well as the host sustaining some self-inflicted collateral tissue damage. During infection with African trypanosomes, both effector and suppressor cells are activated and the balance between these opposing arms of immunity determines susceptibility or resistance of infected host to the parasites. Immune evasion by the parasites could be directly related to parasite factors, (e.g. antigenic variation), or indirectly through the induction of suppressor cells following infection. Several cell types, including suppressive macrophages, myeloid-derived suppressor cells (MDSCs), and regulatory T cells have been shown to contribute to immunosuppression in African trypanosomiasis. In this review, we discuss the key factors that contribute to immunity and immunosuppression during T. congolense infection, and how these factors could aid immune evasion by African trypanosomes. Understanding the regulatory mechanisms that influence resistance and/or susceptibility during African trypanosomiasis could be beneficial in designing effective vaccination and therapeutic strategies against the disease.